Climate Risk Country Profile : Georgia - World Bank Group; Asian Development Bank (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
Georgia is located in the South Caucasus region, sharing land borders with Russia to the north, Turkey to the southwest, Armenia to the south, and Azerbaijan to the east. Over the past two decades, Georgia has experienced significant economic change, urbanization, and displaced populations (due to conflict and disasters triggered by natural hazards). This document aims to summarize the climate risks faced by Georgia. This includes short and long-term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of Georgia, as such this profile potentially overlooks some localized impacts and transboundary flow dynamics. The core data presented is sourced from the database sitting behind the World Bank Group’s climate change knowledge portal (CCKP). This document also aims to direct the reader to many useful sources of secondary data and research.